HPLC mapping of second generation ethanol production with lignocelluloses wastes and diluted sulfuric hydrolysis - Diogo José Horst; Rodolfo R. H. Petter; Rogério de Almeida Vieira; Theodoro Marcel Wagner (Acta Scientiarum: Technology, 2014)
Wood wastes are potential material for second generation ethanol production within the concept of residual forest bio-refinery. Current paper reports on ethanol production employing an HPLC method for monitoring the chemical content dispersed in the hydrolysate liquor after fermented. The proton-exchange technique was the analytical method employed. Twelve types of wood chips were used as biomass, including Hymenolobium petraeum, Tabebuia cassinoides, Myroxylon peruiferum, Nectandra lanceolata, Ocotea catharinensis, Cedrelinga catenaeformis, Cedrela fissilis Vell, Ocotea porosa, Laurus nobilis, Balfourodendron riedelianum, Pinus Elliotti and Brosimum spp. The influence of diluted sulfuric hydrolysis on the yeast Saccharomyces cerevisiae during the fermentation assay was also investigated. Standard compounds mapped in the analysis comprised fructose, lactic acid, acetic acid, glycerol, glucose and ethanol. The yeast showed ethanol productivity between 0.75 and 1.91 g L-1 h-1, respectively, without the addition of supplementary nutrients or detoxification. The use of these materials for the bioconversion of cellulose into ethanol has been proved. Current analysis contributes towards the production of biofuels by wastes recovery and by process monitoring and optimization.